Multi-criteria evaluation of masonry facade installation by saving resources and limiting waste - Zigmund, Viačeslav; Antuchevičienė, Jurgita; Migilinskas, Darius (International Conference “Environmental Engineering”, 2023)
The aim of the study is to offer a new sustainable method for production and installation of masonry facade. The paper presents a case study of facade reconstruction and aims to evaluate three masonry facade alternatives according to multiple criteria, focusing on saving resources and limiting waste. Building Information Model was prepared for precise quantity surveying and management. The Entropy method was applied to determine the relative weights of criteria, and alternatives were evaluated and ranked by applying the CoCoSo (Combined Compromise Solution) method. Prefabricated tension masonry panels were found to be the best sustainable way of masonry façade installation.